An Unbiased Captive Audience: A Study of The Literary Uses of Captivity Narratives - Lance Lee, (The Toro Historical Review, 2025)
This research paper explores the evolution of Native American captivity narratives from the 16th century to the 20th century, emphasizing how personal gain and propagandist motives transformed their historical integrity. These narratives originally provided truthful accounts of the experiences of captured individuals. However, as the genre gained popularity, authors began fabricating stories, and the genre of captivity narratives became flooded with stories that were driven purely by greed or other agendas such as religious propaganda. By studying popular and influential narratives such as those of Hans Staden, John Smith, and Mary Rowlandson, this paper illustrates how narratives transitioned from accurate documentation to vehicles for moral and religious messaging. By the end of captivity narratives' popularity as a genre, these drastic changes in motives culminated in a reversal of roles where Native Americans became the subjects of captivity instead of the captors.